Influence of cigarette smoke on the arginine pathway in asthmatic airways: Increased expression of arginase I - Bergeron, Céline; Boulet, Louis-Philippe; Page, Nathalie; Laviolette, Michel; Zimmermann, Nives; Rothenberg, Marc E.; Hamid, Qutayba (Journal of allergy and clinical immunology, 2007)
Up to 30% of asthmatic subjects are smokers, and smoking might be an important contributor to asthma pathology. Inducible nitric oxide synthase (iNOS), ornithine decarboxylase (ODC), and arginase I are involved in the arginine pathway. We have shown that arginase I and iNOS are upregulated in asthma. Smoking asthmatic subjects are reported to have low exhaled nitric oxide levels. The effect of cigarette smoking on the expression of arginase I in asthma is unknown. The aims of this study were to investigate the expression of arginase I, ODC, and iNOS in asthmatic airways of smokers and nonsmokers and in vitro after nicotine stimulation. Endobronchial biopsies were performed on 24 steroid-naive subjects with mild asthma: 12 smokers and 12 nonsmokers. Arginase I, ODC, and iNOS levels were assessed by means of immunohistochemistry and in situ hybridization (arginase I). In vitro stimulation of airway cells with nicotine was performed, followed by real-time PCR. Arginase I, ODC, and iNOS were expressed in the epithelium and smooth muscle bundles of both subgroups of asthmatic subjects. There was an increase of arginase I and ODC immunoreactivities in smoking compared with nonsmoking asthmatic subjects. There was no significant difference in immunoreactivity for iNOS between groups. Nicotine induced a 2-fold increase in arginase I and ODC expression in airway epithelial cells and fibroblasts. This study demonstrates that the expression of arginase I and ODC is increased in airways of smoking compared with nonsmoking asthmatic subjects and in vitro by nicotine. Increased expression of arginase I might lead to low exhaled nitric oxide and chronic obstructive pulmonary disease–like airway remodeling in smoking asthmatic subjects.